Control strategy of multiple interlinking converters for low-voltage hybrid microgrid based on adaptive droop - Shumin Zong; Yihang Lyu; Can Wang (Energy Reports, 2023)
Distributed generation supply efficiency can be fully realized with the use of a microgrid as a power interface and an efficient operation control technique. The key component of an AC/DC hybrid microgrid is the interlinking converter, which enables flexible power interactions between AC and DC subgrids. This paper proposes an adaptive droop control strategy for multiple ICs in the hybrid microgrid. This control strategy can not only reduce unnecessary power flow between subgrids, but it can also compensate for droop in AC and DC bus voltages. With the proposed control strategy, the problem of inaccurate power distribution and existing circulation caused by the line impedance or capacity difference of ICs can be solved. Taking the island mode of a low-voltage hybrid microgrid as an example, the impact of line impedance on IC transmission power is examined in this paper. As a starting requirement for ICs, the AC/DC bus voltage and the subgrid’s load state are combined. Dead zones are settled to reduce unnecessary power flow. The adaptive droop coefficient is made up of both voltage regulation and power regulation. Voltage regulation maintains the supplied side of the microgrid in its rated state, while power regulation solves issues with power distribution and circulation brought on by line impedance. The adaptive droop link enhances the accuracy of inter-IC power distribution and inter-subgrid power coordination. We verified the validity of the proposed strategy using MATLAB and a hardware-in-the-loop (HIL) experimental platform.